1887 N.M. Laws 56, ch. 30, § 5 - (:unkn) unknown (General Publisher, 1887)
Any person being armed with a deadly weapon, who shall, by words, or in any other manner, insult or assault another, upon conviction thereof, shall be punished by a fine of not less than one hundred dollars, not more than three hundred dollars, or by imprisonment at hard labor in the county jail or territorial penitentiary for not less than three months, nor more than one year, or by both such fine and imprisonment, in the discretion of the court or jury trying the same.
--
Keywords: POSSESSION